A Case Report Exploring Activity Intensity in Inpatient Rehabilitation after Stroke - Kathryn Zalewski; Julie Kerk; Kristina Laundre; Amber Wacek; Melissa Wiedmeyer (Case Reports in Medicine)
Background and Purpose. Inpatient rehabilitation in countries other than the United States (US) has been described as a time where patients are often not engaged in intensive physical activity. The purpose of this case report is to explore the amount and intensity of physical activity provided in inpatient rehabilitation after stroke in the US. Methods. This study presents a case report of a person admitted to an inpatient rehabilitation unit after sustaining a first stroke. A customized data collection tracked type of activity, activity intensity and social interaction every 5 minutes during the rehabilitation day. Results. 74 percent of the day was spent in low intensity, often seated, physical activity; 14% of the day was spent resting or sleeping. Only 2.91% the day was spent in moderate or high intensity activity with a mobility focus. Conclusions. Consistent with other studies, this case report suggests a relatively low physical demand to rehabilitation delivered in inpatient stroke rehabilitation. This case begins to raise questions about optimized rehabilitation parameters for acute stroke rehabilitation.